Correction: Detecting the impact of temperature on transmission of Zika, dengue, and chikungunya using mechanistic models. - Erin A Mordecai; Jeremy M Cohen; Michelle V Evans; Prithvi Gudapati; Leah R Johnson; Catherine A Lippi; Kerri Miazgowicz; Courtney C Murdock; Jason R Rohr; Sadie J Ryan; Van Savage; Marta S Shocket; et al. (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0005568.].